2017
DOI: 10.1371/journal.pone.0176344
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perception of children's nutritional status in the Federal District, Brazil

Abstract: Maternal perception of child's nutritional status has a potential impact on the identification, prevention, and treatment of childhood overweight. Thus, the aim of this study was to evaluate the prevalence of misperception and factors associated with maternal perception of the nutritional status of first- to third-grade elementary school students from private schools in the Federal District, Brazil. This cross-sectional study was conducted with 554 mother-child pairs. Children's nutritional status was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
14
0
3
Order By: Relevance
“…This finding is similar to studies in which they found that mothers tended to underestimate their sons weight status more than their daughters weight status. [19][20][21] In this study, both educated and uneducated mothers misclassified their children's weight status significantly (p=0.00001). Surprisingly, 91.3% of graduate or postgraduate mothers of middle SES perceived their child as NW status while actually only 39.1% were of NW and 52.1% of UW (p=0.00001); this could be due to the fact that most of them were working women, spending less time with their children.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…This finding is similar to studies in which they found that mothers tended to underestimate their sons weight status more than their daughters weight status. [19][20][21] In this study, both educated and uneducated mothers misclassified their children's weight status significantly (p=0.00001). Surprisingly, 91.3% of graduate or postgraduate mothers of middle SES perceived their child as NW status while actually only 39.1% were of NW and 52.1% of UW (p=0.00001); this could be due to the fact that most of them were working women, spending less time with their children.…”
Section: Resultsmentioning
confidence: 56%
“…Younger mothers were more likely to overestimate the nutritional status of their children compared with mothers older than 35 years of age. 21 Similarly, Mothers between 24-35 years of age had lower misperception of children's weight status than mothers < 24 years of age. 25 Conversely, Aparicio G, et al observed that mothers >40 years of age were more likely to misperceive children's weight status.…”
Section: Resultsmentioning
confidence: 96%
“…Maynard et al , for instance, showed that 32% of mothers perceived their children with overweight as having normal weight. Furthermore, mothers were found to underestimate the size of their children with overweight and obesity in 39.3% and 25.3% of instances in Brazil , respectively, and in 80.4% of instances among children with overweight and obesity in Malaysia . This could be due to multiple factors, including different cutoffs used for BMI classification, different tools employed to evaluate parents' perception, or differences in children's ages.…”
Section: Discussionmentioning
confidence: 97%
“…The present paper is part of a larger study that also evaluated maternal perception of children's nutritional status, as well as maternal attitudes, beliefs and practices related to children feeding. The first data on maternal perception of children's nutritional status has already been published [ 1 ]. The current analysis adds new understanding on the factors associated with maternal dissatisfaction with their schoolchildren’s body size.…”
Section: Methodsmentioning
confidence: 99%
“…Family is known to hold meaningful influence over their children’s eating habits, and mothers play an important role on educating and selecting foods for their offspring [ 1 6 ]. Therefore, the way mothers perceive their child's body and the presence of maternal dissatisfaction with their child's body may affect their attitudes and practices related to the child's dietary intake [ 1 , 4 , 7 9 ].…”
Section: Introductionmentioning
confidence: 99%